Hasil Belajar Akuntansi Keuangan Menengah 1 Ditinjau Dari Penguasaan Konsep Akuntansi Dan Kontinuitas Belajar Pada Mahasiswa Pendidikan Akuntansi Universitas Muhammadiyah Surakarta Tahun 2015/2016 - Silviani, Wuri Pratiwi, Dra. Titik Asmawati, SE., M.Si (2016)
The purpose of this research are: 1) To determine the effect of the accounting concept mastery on learning outcomes. 2) To determine the effect of continuity of learning on learning outcomes. 3) To determine the effect of accounting concepts and continuity mastery learning on learning outcomes. This research is descriptive quantitative research with a conclusion through statistical methods. The population in this study were all students of batch 2014 Accounting education who are studying subjects Intermediate Financial Accounting 1. The sample was taken as 131 students by Proportional Random Sampling. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 2.441 + 0.409 X1 + 0.548 X2. The equation shows that the learning outcomes are influenced by the mastery of accounting concepts and continuity of learning. The conclusions drawn are: 1) The control of accounting concepts to effect the learning outcomes are acceptable. This is based on multiple linear regression analysis (t test) note that tcount>ttable, 2.647> 1.960 and the significance value <0.05, namely 0.009 with the effective contribution of 29.7%. 2) Continuity of learning to effect the learning outcomes are acceptable. This is based on multiple linear regression analysis (t test) note that tcount>ttable, namely 3.075> 1.960 and the significance value <0.05, namely 0.003 with the effective contribution of 34.8%. 3) The control of accounting concepts and continuity of learning for effect learning outcomes are acceptable. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 116.074> 3.000 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.645 indicates that the influence mastery of accounting concepts and continuity of learning for learning outcomes amounted to 64.5% while the remaining 35,5% is influenced by other variables outside the study.